Splinters in the fingernails, heart and brain: thromboembolic complications of non-bacterial thrombotic endocarditis despite treatment with a direct-acting oral anticoagulant. Issue 1 (24th January 2022) - Wang, Louis W; Phan, Justin; Schuetz, Priyanka; Omari, Abdullah; Watson, Alasdair J; Subbiah, Rajesh N
ABSTRACT: Non-bacterial thrombotic endocarditis (NBTE) is a rare condition characterized by non-infectious vegetations affecting the cardiac valves. Although systemic thromboembolism is a commonly associated condition, antiphospholipid syndrome is less common. Nevertheless, treatment generally involves long-term anticoagulation. We report a case of a patient with previously undiagnosed NBTE who suffered systemic thromboembolic events despite pre-existing treatment with a direct-acting oral anticoagulant.